Dynamics of soil properties and bacterial community structure by mulched fertigation system in semi-arid area of Northeast China - Wang,Ling; Wang,Meng; Li,Qian; Zhang,Jinjing; Li,Cuilan; Yuan,Yuhan; Tan,Pan; Liu,Hang (PeerJ, 2022)
The agricultural irrigation and fertigation systems have a non-negligible impact on the soil microenvironment in arid and semi-arid areas. Therefore, studying the processes and changes of soil microenvironment under different plastic mulch drip irrigation systems can reveal the “soil-microbe” mechanism and provide a theoretical support for the optimal irrigation and nutrition management of maize in the semi-arid area of Northeast China. Three treatments were used for this study in the semi-arid area of northeast China, namely; mulched fertigation system (MF), drip irrigation system (DI), and farmers’ practices system (FP). We used high-throughput sequencing to study the soil bacterial community structure targeting the 16S rRNA gene. The agricultural irrigation and fertigation systems significantly affected soil properties. MF significantly increased bacterial abundance and bacterial diversity and richness. Moreover, MF and DI markedly increased some relative abundance of beneficial bacterial. The bacterial network in MF was more conducive to the health and stability of the agroecosystem and the relationships among species in MF bacterial network were more complex. The agricultural irrigation and fertigation systems had indirect effects on community composition and bacterial diversity through soil organic carbon (SOC), ammonium nitrogen ( ${NH}_{4}^{+}$ NH 4 + -N), nitrate nitrogen ( ${NO}_{3}^{-}$ NO 3 − -N), pH, moisture, ${NH}_{4}^{+}$ NH 4 + -N and ${NO}_{3}^{-}$ NO 3 − -N had indirect effects on yield through bacterial community composition, bacterial diversity and bacterial abundance. These findings suggested that MF was the most effective treatment to improve soil bacterial abundance and diversity, and stabilize the functional quality of soil biological processes.
Keywords: Bacterial community; Illumina MiSeq sequencing; Mulched fertigation; Soil properties